Gesturing Beyond Modernism: Frank O’Hara, Metonymy, and the Performing Self - Levi, Melih (American Studies in Scandinavia, 2022)
This article studies the changing role of metonymy in Frank O’Hara’s poetry. In his early work, O’Hara often uses metonymy for the referential assortment of various modernist fields of influence. The origins of O’Hara’s signature ‘I do this, I do that’ style can be traced back to the problems of self-consciousness which emerge in these early homages to modernism. Though he is often celebrated for the swift responsiveness and spontaneity of his urban poetry, these metonymic homages reveal a poet with deeper and longer attachments in the object-world. Such attachments alert O’Hara to the risk of turning the self into one of the concrete or objectual signifiers of his metonymic assemblages. O’Hara’s early negotiation with the descriptive legacies of modernism and the resulting anxiety about self-consciousness will be demonstrated through an analysis of his sestina, “Green Words.” O’Hara’s solution will entail changing the logic of metonymy from contextual assemblage, where the body often finds representation as a conceptual object, to a foregrounding of the inherently metonymic character of bodily and gestural expression, where the body emerges as a dynamic and responsive presence. Thus, this article investigates how O’Hara’s ekphrastic accounts of contemporary art allowed him to break away from modernism to embrace a poetics of embodied responsiveness.